ANALISIS PENGARUH INDIKATOR MAKRO EKONOMI TERHADAP INDEKS HARGA SAHAM LQ 45 DI BURSA EFEK INDONESIA - Arifin, Pramesti Regita; Khalifaturofiah, Sholikha Oktavi (Buletin Studi Ekonomi, 2023)
Stock price fluctuations in the capital market can be influenced by macroeconomic conditions. This study intends to analyze the effect of macroeconomic indicators, namely inflation, the rupiah exchange rate, interest rates and economic growth on the LQ 45 stock price index. This study uses a quantitative approach with monthly time series data types for the 2017:1-2021:12 period. Data analysis was performed using a multiple linear regression model. The results showed that partially inflation and economic growth had no significant effect on the LQ 45 stock price index. The rupiah exchange rate had a significant negative effect on the LQ 45 stock price index. The interest rate has a significant positive effect on the LQ 45 stock price index. The implication of this research is that to increase the LQ 45 stock price index, government policies are needed that can stimulate an increase in interest rates and strengthen the rupiah exchange rate.